London Trauma Conference 2015. Issue 1 (June 2016) - Avery, Pascale; Salm, Leopold; Bird, Flora; Hutchinson, Anja; Matthies, Ashley; Hudson, Anthony; Jarman, Heather; Nilsson, Maria; Konig, Tom; Tai, Nigel; Fevang, Espen; Hognestad, Børge; et al.
Table of contents I1: Trauma, Pre-hospital and Cardiac Arrest Care 2015 Pascale Avery, Leopold Salm, Flora Bird A1: Retrospective evaluation of HEMS 'Direct to CT' protocol Anja Hutchinson, Ashley Matthies, Anthony Hudson, Heather Jarman A2 Rush hour – Crush hour: temporal relationship of cyclist vs. HGV trauma admissions. A single site observational study Maria Bergman Nilsson, Tom Konig, Nigel Tai A3 Semiprone position endotracheal intubation during continuous cardiopulmonary resuscitation in drowned children with regurgitation: a case report and experimental manikin study Espen Fevang, Børge Hognestad, Håkon B. Abrahamsen A4 An audit of CO2 A-a gradient in non-trauma patients receiving pre-hospital anaesthesia Olivia V Cheetham, Matthew JC Thomas, Kieron D Rooney A5 Can the use of c-spine immobilisation collars be avoided in non-trauma patients presenting to the Emergency Department? Josephine Murray, Malcolm Tunnicliff A6 Curriculum mapping in ED point of care simulation Joseph W Collinson, Thomas Brown, Christopher Pritchett A7 Point of care multidisciplinary trauma team simulation & participant satisfaction in a geographically remote trauma unit in Cornwall Christopher SA Pritchett, Mark Jadav, Gareth Meredith, Jamie Plumb, Steve Harris, Roger Langford A8 Conservative management of head injury inpatients - the challenge of simplifying injury management in a non-neurosurgical hospital JG Hunter, A Sage, R Madden, O Flamank, B Broadbent, S Marsh, H Lewis, E Daniels, N Roberts A9 Improving the care of traumatic brain injury at non-neurosurgical hospitals: Introducing a head injury pathway and single place of care is associated with significant improvements in neurological observation JG Hunter, A Sage, R Madden, O Flamank, B Broadbent, S Marsh, H Lewis, E Daniels, N Lin, N Roberts A10 The experience of inter-disciplinary students undertaking cardiac arrest moulage training Samuel Bulford, Silas Houghton-Budd, Sam Pearson, Megan Clear-Hill A11 Impact brain apnoea – nine cases David J Menzies, James P Leonard, Conor Keogh, Ray Quinn, John D Hinds A12 Time well spent? Improving the performance improvement programme in a busy Trauma Unit N Roberts, D Ashton-Cleary, M Jadav A14 Clinical significant and outcome of pulmonary contusions in patients with blunt chest trauma Ismail Mahmood, Ayman El-Menyar, Basil Younis, Ahmed Khalid, Syed Nabir, Mohamed Nadeem Ahmed, Omer Al-Yahri, Hassan Al-Thani A15 Plastics operative workload in major trauma centres: a national prospective survey Katie Young, Susan A. Hendrickson, Georgina Phillips, Matthew D. Gardiner, Shehan Hettiaratchy A16 A survey to assess the accuracy of estimating height by pre-hospital clinicians: can we reliably predict those most at risk of serious injury? Alexandra Alice Crossland, Anthony Hudson A17 An audit of the cause, outcome and adherence to treatment Standard Operating Procedure (SOP) for all traumatic cardiac arrests at a Helicopter Emergency Medical Service over a 12-month period Nicholas C Brassington, Anthony Hudson, Emily McWhirter A18 Should we "stay-and-play? A study of patient physiology in Norwegian Helicopter Emergency Services Bjørn O Reid, Marius Rehn, Oddvar Uleberg, Andreas J Krüger A19 Training in resuscitative thoracotomy: have we cracked it? A survey of higher Emergency Medicine trainees in London Cara Jennings, Yasmin Kapadia, Duncan Bew A20 London's Air Ambulance (LAA): 25-years of drownings in an urban environment Jenny Townsend, Tom P Hurst, Elizabeth A Foster A21 Live patients in trauma simulation – more than just simulation on a shoestring? Thomas B Brown, Joseph Collinson, Christopher Pritchett, Toby Slade A22 Collecting core data in pre-hospital critical care using a consensus based template Kristin Tønsager, Marius Rehn, Kjetil G.Ringdal, Andreas J.Krüger A23 Prehospital interventions before and after implementation of a physician staffed helicopter Rasmus Hesselfeldt, Sandra Wulffeld, Asger Sonne, Lars S. Rasmussen, Jacob Steinmetz A24 Duration of ventilation following prehospital drug assisted intubation; a retrospective review Thomas J Renninson, Nadine Thomson, Harvey Pynn, Timothy J Hooper A25 Non-haemorrhagic shock in trauma: a novel guideline for management in ED Anthony Hudson, Jacinta Dawson, Ashley Matthies A26 Patient-tailored triage decisions by anaesthetist-staffed pre-hospital critical care teams Morten Langfeldt Friberg, Leif Rognås A27 Anatomical accuracy and appropriate sizing of pre-hospital thoracostomies Jessica FG Wills, Anthony Hudson A28 Pre-hospital management of mass casualty civilian shootings Conor DA Turner, Marius Rehn A30 The prevalence of alcohol-related trauma recidivism: a systematic review James Nunn, Mete Erdogan, Robert S. Green A31 Development of a hospital-wide program for simulation-based training in trauma care and management Samuel Minor, Mete Erdogan, Kathy Hartlen, Robert S. Green A32 Out of Hospital Cardiac Arrests (OOHCA); lessons from Hollywood Ruth Bird, Rachael L. Grupping A33 Mechanism of injury as a predictor of severity of injury in road traffic collisions: a literature review Amelia M. Stacey, Marius Rehn, David J. Lockey A34 Lessons to be learned from prehospital airway intervention documentation? Are airway intervention documentation templates as successful in-hospital as prehospitally? S. Abiks, L. Cutler, K. Monaghan, A. Al-Rais, C. Hymers, R. Bloomer, Y. Kapadia A35 Novel biomarkers inpre hospital management oft raumaticb raini njury (the PreTBI study protocol) Sophie-Charlott Seidenfaden, Ingunn S. Riddervold, Hans Kirkegaard, Niels Juul, Morten T. Bøtker A36 Hospital outcomes of traumatic railway incidents: a seven-year observational retrospective study of a major trauma centre Alice Gao, Zane Perkins; Gareth Grier, Alex Tzannes A37 Does taking a third crew member affect the on-scene time of HEMS jobs? Nathan Hudson-Peacock, Quentin Otto, Laurie Phillipson, Rik Thomas, Ainsley Heyworth A38 Does pre-hospital rapid sequence induction affect on-scene time of HEMS jobs? Quentin Otto, Nathan Hudson-Peacock, Laurie Phillipson, Ainsley Heyworth, Erica Ley A39 Code red: shock index as a prehospital indicator of massive haemorrhage Daniel Banner, Ainsley Heyworth, Erica Ley A40 Air ambulance tasking: how accurate are our current methods? Madeleine Benson, Nathan Hudson-Peacock, Tony Stone, Erica Ley, Louise Rousson, Ainsley Heyworth A41 Modern trauma burden in a district general hospital Beth A Lineham, Matthew J Lee, Martin Gough A42 Establishing a legal service for major trauma patients in two UK major trauma centres William H Seligman, Hannah E Thould, Andrew Dinsmore, Charlotte Tan, Julian Thompson, C Andy Eynon, David J Lockey A43 Prehospital assessment and care of patients – a study of the use of guidelines when assessing head trauma Rebecka M Rubenson Wahlin, Veronica Lindström, Sari Ponzer, Veronica Vicente A44 An audit of pre-hospital blood pressure management resulting from head injury Pamela Eligio, Anthony Hudson A45 The surgical contribution of surface shading volumetric rendering techniques in rib fracture management Robert Young, Dimitri Amiras, Ian Sinha